Alveolar rhabdomyosarcoma of the vulva in an adult: a case report and literature review. Issue 3 (March 2020) - He, Weihua; Jin, Yue; Zhou, Xinhui; Zhou, Ke; Zhu, Rong
Rhabdomyosarcoma (RMS) is a common soft tissue tumor in children, but it is rare in adults. Alveolar rhabdomyosarcoma (ARMS) is a subtype of RMS and is extremely rare in adults, especially concerning the genital tract. We report a case of a 20-year-old woman who was admitted to and treated in our hospital for an RMS of the vulva. The patient presented with local recurrence and bone metastasis during chemotherapy after surgery and died within 1 year of diagnosis. Based on a literature review, the prognosis of ARMS in adults is poor. The treatment strategy for ARMS is not well established yet. The lungs and bone are two common sites of metastasis of ARMS.